DFT Study in Strain Engineering HfSe2 Nanosheets for Sensing SO2, SOF2, and SO2F2 Gases - Noora Ali; Lafy F. Al-Badry; Ali Ben Ahmed (مجلة علوم ذي قار, 2025)
Strain engineering is a technique of tuning a material's properties by modifying its mechanical or structural characteristics. Using first-principles calculations, the strain impact on the electronic structure of layered HfSe2 nanosheets has been studied to examine the sensing capabilities of the layered HfSe2 nanosheets to three SF6 decomposition compounds (SO2, SO2F2, and SOF2). With biaxial strain, the band gap of the surfaces under discussion expands with tensile up to 1% and gradually decreases for strains between −1% and −5%. Additionally, our findings demonstrate that biaxial strains have a significant impact on the electronic characteristics, adsorption energy (Ead), and desorption time of SO2, SOF2, and SO2F2 adsorbed HfSe2 systems. The highest adsorption impact of SO2, SOF2, and SO2F2 on the bilayer of HfSe2 occurred at a compressive strain of −5%, with the Ead determined as −1.34, −1.27, and −1.31 eV, respectively. These external factors are widely preferred and offer a workable solution for tunable HfSe2-based gas sensors and electrical devices under biaxial compressive strain.